1990
DOI: 10.1128/iai.58.4.970-977.1990
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the cloned gene for enterotoxin STb of Escherichia coli

Abstract: This study involved the construction of hybrid plasmids to produce heat-stable enterotoxin type II of Escherichia coli (STb). The translation of the open reading frame for the STb gene estA was demonstrated in several ways. Studies using in vivo labeling with [35S]cysteine demonstrated a radiolabeled protein band on sodium dodecyl sulfate-polyacrylamide gel electrophoresis of the expected molecular weight of 5,000 for toxin STb. Insertion of translational or transcriptional termination signals into the Bglll s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…However, the antibody titer remained low despite several booster doses, and the serum could not neutralize STII activity. Lawrence et al (16) reported the production of anti-STII serum by the injection of a fusion protein (OmpF-STb fragment-1-galactosidase) or a 19-amino-acid peptide. The serum reacted weakly at low dilutions with the enterotoxin in the culture supernatant.…”
Section: Discussionmentioning
confidence: 99%
“…However, the antibody titer remained low despite several booster doses, and the serum could not neutralize STII activity. Lawrence et al (16) reported the production of anti-STII serum by the injection of a fusion protein (OmpF-STb fragment-1-galactosidase) or a 19-amino-acid peptide. The serum reacted weakly at low dilutions with the enterotoxin in the culture supernatant.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo radiolabeling experiments with [35S]cysteine showed that culture supernatants contained a labeled band with a molecular weight of about 5,000 on sodium dodecyl sulfate-polyacrylamide gel electrophoresis, which would represent STb (8,13). Similarly, Kupersztoch et al (11) identified the extracellular mature form of STb with a molecular weight of 5,200.…”
Section: Discussionmentioning
confidence: 98%
“…Other workers have produced antibodies against the fusion proteins protein A-STb (9) or OmpF-STb-p-galactosidase (13) or against the synthetic peptide coupled to keyhole limpet hemocyanin (13). However, such fusion proteins are poorly active or nonactive in pig intestinal loops (9,13). In addition, antibodies directed against such fusion proteins may demonstrate cross-reactivity with non-STh-producing strains.…”
Section: Discussionmentioning
confidence: 99%
“…STb induces intestinal secretion in newborn pigs and weanling-age pigs (391) but has no apparent activity in mice. STb is produced by porcine)(K88-positive) ETEC (202), and the mechanism by which it stimulates the intestinal mucosa to secrete is unknown (187,391). STa is produced by K99, F41, and 987P ETEC strains.…”
Section: Enterotoxinsmentioning
confidence: 99%